Exercise behaviour and the determinant factors among medical students before and during the COVID-19 pandemic - Griadhi, Adiartha; Sundari, Luh Putu Ratna; Sutarsa, I Nyoman (Public Health and Preventive Medicine Archive, 2022)
Background and purpose: Students’ physical activity levels decreased significantly after college enrollment. Disruption during the COVID-19 pandemic also affects the students’ exercise level. The psychological aspect and the academic situation of medical students could interact with pandemic disruption differently compared to other students. This study compares exercise behaviour and its determinant factors among medical students before and during the pandemic. Methods: This study was conducted by collecting data in August 2021 and then comparing it to our data collected in July 2011. Participants were determined by a proportional random sampling based on gender and education year. There were 127 and 205 research participants in 2011 and 2021. The exercise behaviour and determinant factors were based on the Transtheory Model of behavioural change and grouped into five stages of exercise levels and four categories of factors. The data were analyzed descriptively and comparison tested for the two years. Results: This study showed a significant increase in exercise behaviour among medical students during the pandemic (p<0.05). The number of students in the pre-contemplation, contemplation, and preparation stages has decreased, and those in action and maintenance stages doubled compared to the pre-pandemic period. The change in exercise behaviour showed that changes only occurred in female and clinical-year students (p<0.05). There was no significant change in male and pre-clinical medical students. Predisposing, enabling, and maintenance factors are determinants of exercise behaviour that increased significantly during the pandemic (p<0.05), and personal factors did not increase significantly. Conclusion: Female and clinical-year medical students’ exercise activity increased significantly during the pandemic. Predisposing, enabling, and maintenance factors also increased substantially during the pandemic, while personal factors did not change significantly. Gender-related psychological and behavioural reactions to COVID-19 pandemic disruption explain these results.